Lung Volume and Pneumatization Changes in Children in Early Post-Surgical Period After Correction of Severe Neuromuscular Scoliosis Complicated with Respiratory Failure: Cohort Study - Anna V. Makarova; Mudhar A.А. Alshaowa; Оlga S. Maslak; Аlexandr Yu. Mushkin (Вопросы современной педиатрии)
Background. The effect of spinal deformity surgical correction in children with severe neuromuscular scoliosis (NMS) on lung function remains unexplored. Objective. The aim of the study is to — to survey the dynamics of volume and structure of lungs pneumatization in children after surgical correction of severe neuromuscular deformities of the spine complicated by respiratory disorders. Methods. CT scans of lungs from 5 children with right-sided NMS, grade IV (Cobb angle > 50°) and functional respiratory disorders (lung capacity < 30% of normal value according to spirometry data and/or clinical signs of respiratory failure) were retrospectively studied. Right and left lungs volumes, their ratio (asymmetry index), indicators of distribution of tissue density of each lung (as a percentage of total volume) before (not earlier than 2 months) and after (not later than 3 months) surgical correction of scoliosis were determined via the data processing from CT scans of the thoracic spine. Results. All children had both lung volumes below reference values (healthy peers) before surgery. The right lung volume increased by 11% (6.4–40.6%), the left lung — by 41% (22.5–90%) with the asymmetry index approaching the reference values for the corresponding age after correction of spinal deformity (the value of scoliotic deformity decreased (median) from 94 to 68°). The volume of normal ventilation zones increased from 30 to 50% on the right side, and from 41 to 55% on the left side, primarily due to decrease in the volume of hypoventilation zones, but not atelectasis and emphysema. Conclusion. Surgical correction of spinal deformity in children with NMS, grade IV, complicated with respiratory failure led to normalization of lungs volume and tissue density characteristics already in the early postoperative period.